2021
DOI: 10.1101/2021.02.04.429503
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population genetics as a tool to elucidate pathogen reservoirs: Lessons fromPseudogymnoascus destructans, the causative agent of white-nose disease in bats

Abstract: Emerging infectious diseases pose a major threat to human, animal, and plant health. The risk of species-extinctions increases when pathogens can survive in the absence of the host, for example in environmental reservoirs. However, identifying such reservoirs and modes of infection is often highly challenging. In this study, we investigated the presence and nature of an environmental reservoir for the ascomycete fungus Pseudogymnoascus destructans, the causative agent of white-nose disease. We also characteris… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 70 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…The tidyverse collection of packages (Wickham et al, 2019) was used to improve ease and efficiency in analyses and the corrplot package (version 0.90, Wei & Simko, 2017) was used for visualization of correlations of relative frequencies of genotypes occurrence. The R-script used for analyses as well as the raw data are available from Dryad (https://doi.org/10.5061/dryad.x0k6d jhhx; Fischer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The tidyverse collection of packages (Wickham et al, 2019) was used to improve ease and efficiency in analyses and the corrplot package (version 0.90, Wei & Simko, 2017) was used for visualization of correlations of relative frequencies of genotypes occurrence. The R-script used for analyses as well as the raw data are available from Dryad (https://doi.org/10.5061/dryad.x0k6d jhhx; Fischer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To examine this, we simulated bottlenecks of different strengths (i.e., sampled isolates; in steps of 1 from 2 to 3100) by subsampling the pool of genotyped isolates from the walls in Eldena, mimicking the subset of spores passed from the walls to the bats (each winter season investigated separately). As previous studies have shown that only a fraction of spores germinates, we subsequently randomly selected 17.5% of the previously subsampled isolates for further analyses (based on the mean germination rate for spores of P. destructans from the data in Fischer et al, 2020; mean = 17.5%). For each value of bottleneck strength (i.e., sample size), we then calculated the genotypic richness (i.e., number of genotypes) observed in the subsampled data set.…”
Section: How Many Spores Of P Destructans Are Transferred From the Wa...mentioning
confidence: 99%
See 3 more Smart Citations